Analisis Pembelajaran Media Youtube Pada Kanal Mau Tau Banget Dalam Pembelajaran Menulis Teks Eksposisi - Thessalonica, Vero; Sudiana, I Nyoman; Wendra, I Wayan (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This research aims to describe (1) the steps of using YouTube media on the "Mau Tau Banget" channel in teaching students to write exposition texts, (2) the obstacles faced by teachers and students in teaching students to write exposition texts, and (3) the learning outcomes of writing exposition texts after using YouTube media on the "Mau Tau Banget" channel in the teaching process. This research uses a qualitative descriptive research design. The research subjects are the Indonesian Language teacher of class VIII F. The data collection methods used are observation, interviews, and documentation. The data in this research are analyzed descriptively qualitatively. The results of this research show (1) the steps include three activities, namely the opening, core, and closing activities during the implementation of teaching exposition texts. (2) The obstacles found by the teacher indicate several challenges faced by the Indonesian Language teacher in terms of students' abilities to listen and create exposition texts, students' focus on learning exposition texts is still lacking, and the use of time is not yet effective. (3) The learning outcomes provide an overview of the extent of students' abilities in writing exposition texts using YouTube media on the "Mau Tau Banget" channel, seen from the students' work assessed by the teacher, ordered according to their abilities, starting from the highest to the lowest scores. The suggestion of this research is that Indonesian Language teachers should maintain the effectiveness of using YouTube media in teaching.